2013
DOI: 10.1007/s00436-012-3268-0
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal activity of essential oils from five endemic conifers of New Caledonia on the cattle tick Rhipicephalus (Boophilus) microplus

Abstract: The aim of the present study was to demonstrate acaricidal activity on the cattle tick Rhipicephalus (Boophilus) microplus of essential oils from endemic conifers of New Caledonia in the context of the development of natural alternatives. Acaricidal activity of essential oils extracted from resin and heartwood of five endemic conifers of New Caledonia (Araucaria columnaris, Agathis moorei, Agathis ovata, Callitris sulcata, and Neocallitropsis pancheri) was evaluated on 14- to 21-day-old Rhipicephalus microplus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 18 publications
0
15
0
3
Order By: Relevance
“…These alternatives may include new chemistry and/or the identification of novel or underutilized biochemical targets. Several essential oils have been shown to be toxic to the cattle fever tick (R. annulatus) and to the southern cattle tick (R. microplus) [8,22,26,36,37,39,40,46]. Here, we report on the development of an expression system for the southern cattle tick's tyramine receptor (RmTAR1), and present evidence that this receptor may be a potential target of biopesticides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These alternatives may include new chemistry and/or the identification of novel or underutilized biochemical targets. Several essential oils have been shown to be toxic to the cattle fever tick (R. annulatus) and to the southern cattle tick (R. microplus) [8,22,26,36,37,39,40,46]. Here, we report on the development of an expression system for the southern cattle tick's tyramine receptor (RmTAR1), and present evidence that this receptor may be a potential target of biopesticides.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been a growing interest in the use of botanical acaricides, particularly essential oils, to control R. microplus and R. annulatus [8,22,26,36,37,39,40,46]. For instance, the essential oil from cumin seeds (Cuminum cyuminum) and allspice berries (Pimenta dioica) resulted in 100% mortality at concentrations between 2.5% and 20% (v/v).…”
Section: Introductionmentioning
confidence: 99%
“…[9,19,20]. The non-strong acaricidal activity observed may due to the low proportion of compounds with acaricidal potential.…”
Section: Acaricidal Activities Of the Essential Oilmentioning
confidence: 99%
“…Plant extracts with acaricidal activity provide a potential alternative as a substitute for synthetic acaricides currently used for tick control, since promising results have been obtained through testing some plant extracts against R. microplus [5,6,7,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Lago et al [40] studied the composition of six species of Baccharis (Southeast of Brazil) and also detected bicyclogermacrene in the essential oil samples. Lebouvier et al [41] identified that the essential oil from five species of conifer primarily consisted of bicyclogermacrene, and this essential oil was effective as a natural acaricide.…”
Section: Effect Of Organic Fertilizer Doses On the Plant Growth Essementioning
confidence: 99%